Successful use of phlebotomy to treat severe secondary polycythemia due to chronic lung disease - Jacob Fuqua; Josephine Reece; Sarah Sofka (Hematology Reports, 2021)
Secondary polycythemia (SP) occurs as a result of increase erythropoietin levels most commonly as a result of tissue hypoxia. Symptoms such as erythromelalgia, pruritis, and bleeding, which are frequently seen in polycythemia vera (PV), do not commonly occur in SP. Phlebotomy is considered one of the mainstays of therapy for PV but is rarely used for treatment of SP due to concern about worsening tissue hypoxia. We present the case of a patient with severe SP due to chronic hypoxic lung disease who presented with erythromelalgia, pruritis, and bleeding and was treated successfully with therapeutic phlebotomy. This case illustrates the importance of considering the use of therapeutic phlebotomy in symptomatic patients with severe SP.